2020
DOI: 10.36129/jog.32.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital Distance and Gynaecological Diseases: A Narrative Review

Abstract: La distanza anogenitale (AGD) (ovvero la distanza misurata dall'ano al tubercolo genitale) è una caratteristica corporea androgeno-dipendente, che risente dell'esposizione ormonale intrauterina. Studi sull'uomo hanno evidenziato che alterazioni della AGD possono essere associate a malattie dell'apparato riproduttivo, sia negli uomini che nelle donne. In particolare, studi recenti suggeriscono una correlazione tra differenze nella lunghezza della AGD e presenza di patologie ginecologiche, come l'endometriosi e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Ano Genital Distance (AGD) is a sexually dimorphic characteristic that depends on intrauterine androgen exposure. Ano Genital Distance is the distance measured from the anus to the genitals (Crestani et al, 2020;Buggio et al, 2020). Experimentally, AGD at birth reflects the presence of androgen hormone exposure during prenatal life and is considered to be a sensitive lifetime marker of androgen exposure (Kulaksiz & Toprak, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ano Genital Distance (AGD) is a sexually dimorphic characteristic that depends on intrauterine androgen exposure. Ano Genital Distance is the distance measured from the anus to the genitals (Crestani et al, 2020;Buggio et al, 2020). Experimentally, AGD at birth reflects the presence of androgen hormone exposure during prenatal life and is considered to be a sensitive lifetime marker of androgen exposure (Kulaksiz & Toprak, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Pain that is felt due to excessive pathological uterine contractions which the results of clinical examination do not feel any lesions in the small pelvis, while secondary dysmenorrhea is caused by the discovery of lesions in the smaller pelvis such as endometriosis, chronic pelvic inflammation, uterine fibroid cervical stenosis, and abnormalities anatomy and function of other reproductive organs (Taylor et al, 2020;Barcikowska et al, 2020). Studies say that shorter AGD have a higher risk of endometriosis, while long AGD are associated with an increased risk of PCOS (Buggio et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the only other review on this relationship is a narrative literature review by Buggio et al (30). However, several recent studies have reported evidence that supports the hypothesized associations of AGD with gynecological disorders, which prompted us to summarize the findings in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The etiopathogenesis is not clear, and the most approved theory explains the retrograde transplantation of endometrial tissue through the fallopian tubes [2]. Meanwhile, Buggio et al [6] suggest that a prenatal exposure to environmental estrogen will result in a comparatively shorter anogenital distance, which may serve as a secondary marker of higher risk of developing endometriosis later in life.…”
Section: Introductionmentioning
confidence: 99%